Immune response in rhesus macaques after mixed modality immunisations with DNA, recombinant adenovirus and recombinant gp120 from human immunodeficiency virus type 1. - Vinner, L; Therrien, D; Wee, E; Laursen, I; Hanke, T; Corbet, S; Fomsgaard, A (2006)
The establishment of effective regimens for a vaccine against human immunodeficiency virus type 1 (HIV-1) is urgently needed. In the present study we have produced HIV-1 gp120 from a vaccine-relevant primary R5 isolate in recombinant vaccinia (rVV)-infected Vero cells. We have investigated the effect of boosting with this protein in mixed modality immunisations of rhesus macaques following different immunisation. As reported earlier, animals were primed with codon-optimised HIV-1(BX08)env DNA delivered as plasmid or as replication-deficient recombinant human adenovirus type 5 (rAd5), which both induced specific antibody and cellular immune responses (1). Boosting with rAd5 temporarily had increased the anti-gp120 antibody titres approximately 1 log (rAd5+rAd5) or 3 log (DNA+rAd5) (1). However, secondary rAd5 boosting showed less effect due to the induced vector-specific immunity. To further boost the antibody response, the rgp120(BX08) was injected with Quadri A saponin adjuvant. The protein boosting resulted in a 1-2 log antibody increase and also boosting of the cell-mediated immune response. Neutralising antibodies to the heterologous HIV-1(MN) were detected; however, neutralising antibodies to the primary HIV-1(Bx08) isolate were seen only transiently after rAd5 but not the rgp120 immunisation. It is concluded that the rgp120(Bx08) reagent from rVV-infected Vero cells is functional and immunogenic in macaques, inducing both antibody and cellular immunity. The rgp120(Bx08) is a relevant model antigen that may be used to boost antibody and cellular immunity in mixed modality vaccine regimens against HIV-1 in higher animals.